Advanced astrophysics - Duric, Neb (Cambridge, Cambridge University Press, 2004)
Astronomy describes the mechanics of the universe in the more basic language of physics, otherwise known as "astrophysics". Knowledge of black holes, quasars and extrasolar planets requires understanding of the physics underlying astrophysics. This book clarifies the fundamental principles of the field as well as the important astronomical phenomena it describes. Readers will gain a greater appreciation of the connection between physics and astronomy.
Includes bibliographical references.; Index 294-296p.
Keywords: Astronomy; Mathematics; Physical astronomy